(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Policy Implementation is one of the stages of public policy between the formation of policies and the consequences of policies for the people they influence, the objectives of the policies. The purpose of this study is to find out whether there is an influence on policy implementation on employee performance. Policy implementation variables were measured and assessed using five dimensions and employee performance variables were measured and assessed using twelve indicators. The method used in this study is a quantitative method that is measured using statistics. Data collection techniques used were observation and distribution of questionnaires or questionnaires distributed to forty respondents. The results of the validity and reliability tests indicate that each statement item used is valid and reliable. Then from the results of simple linear regression analysis shows that every 1% addition to the value of the variable policy implementation, then the value of the variable employee performance increases by 0.420, and it can be said that the direction of the variable influence on policy implementation to employee performance is positive and significant. From the results of correlation analysis shows that the correlation value is 0.420, which means the level of the relationship between policy implementation variables with the variable employee performance is included in the category of perfect correlation. Thus, it can be concluded that the proposed hypothesis can be tested empirically and with the underlying theories, and it is suggested to the parties concerned to continue to improve the quality of existing services and to continue to build public trust. Keyword: Policy Implementation, Employee Performance, Standart Operating Procedure